2011
DOI: 10.1177/1049732311404903
|View full text |Cite
|
Sign up to set email alerts
|

Heading Into Fatherhood—Nervously: Support for Fathering From Online Dads

Abstract: Men are becoming increasingly aware of and keen about the promises of involved fathering, and there is growing recognition of the need to support fathers, especially in the postnatal period. However, there is limited evidence of how best to offer this support. In this article, we investigate a new avenue of support that is gaining popularity in the public health sector: the Internet. Using qualitative methods, we examine messages in an asynchronous online chat room for new fathers to reveal how fathers themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 85 publications
6
67
0
1
Order By: Relevance
“…Fathers discuss challenges of fatherhood online and look to encourage and confirm one another [12]. They also rely on humor to offer social support to one another [13]. Both mothers and fathers share photos of their babies on Facebook, though mothers report doing this slightly more frequently than fathers do [5].…”
Section: Parents and Internet Usementioning
confidence: 96%
“…Fathers discuss challenges of fatherhood online and look to encourage and confirm one another [12]. They also rely on humor to offer social support to one another [13]. Both mothers and fathers share photos of their babies on Facebook, though mothers report doing this slightly more frequently than fathers do [5].…”
Section: Parents and Internet Usementioning
confidence: 96%
“…An Australian study of a small chat room for new fathers showed they request and share social support using humor and self-disclosure [16]. A second study of the same dataset showed that fathers observed a lack of social spaces, support, and services for new fathers [42].…”
Section: Parents Onlinementioning
confidence: 98%
“…There is compelling evidence which suggests that men/fathers prefer to seek information and support via the internet. It is a good medium with which to engage otherwise hard-to-reach individuals (Fletcher & St George, 2011;Fletcher, Vimpani, Russell, & Keatinge, 2008;Hudson, Campbell-Grossman, Fleck, Elek, & Shipman, 2003).…”
Section: Implications For Clinical Practicementioning
confidence: 99%